Language Style and Emotional Expression Used by Christy Beam in Miracles from Heaven Movie: A Sociolinguistic Study - Putri Afriani Siallagan; Sondang Manik; Rotua Elfrida (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
Language style and emotional expression play significant roles in human communication because they reflect social relationships, communicative purposes, and psychological conditions. In sociolinguistics, language variation is influenced by social contexts and interactions among speakers. This study aims to analyze the types of language styles used by Christy Beam in Miracles from Heaven (2016) and to identify the emotional expressions reflected in her dialogues. The study focuses on the relationship between language style and emotional expression as represented through the main character’s interactions with family members, doctors, and other individuals. This research employed a descriptive qualitative method. The data source was the movie Miracles from Heaven, directed by Patricia Riggen, while the data consisted of Christy Beam’s dialogues. Data were collected through repeated observation, transcription, classification, and interpretation based on Martin Joos’ theory of language styles and theories of emotional expression. The findings reveal that all five language styles proposed by Joos were present in the movie, namely frozen, formal, consultative, casual, and intimate styles. Consultative, casual, and intimate styles were the most dominant, each accounting for 26.67% of the total data. Furthermore, six types of emotional expressions were identified: anxiety, love/affection, anger, fear, happiness, and sadness. Anxiety emerged as the most dominant emotional expression, representing 33.97% of the data. The findings indicate that Christy Beam’s language choices are strongly influenced by social relationships, communication settings, and interaction purposes, while her emotional expressions reflect her psychological experiences as a mother struggling to support her daughter through a serious illness.